Injury Patterns in Fencing Athletes - A Retrospective Review - Emily R Cross; Sloane M Lynch; Patricia E Miller; Danielle L Hunt; Cynthia J Stein (North American Sports Medicine Institute, 2024)
# Background Fencing is a unique and increasingly popular sport, but limited data exist regarding related injuries. # Purpose To examine the types of injuries incurred by fencing athletes, and to analyze associations between age, sex, and hand dominance with type and location of injury. # Study Design Cross-sectional # Methods Retrospective chart reviews were performed to evaluate fencing related injuries in athletes evaluated in the sports medicine and orthopedic clinics of a large teaching hospital. # Results One hundred and eighty-six patients (98 male, 88 female) were included. Average age at time of injury was 14.6 years (range 9 - 32 years). 73% of injuries involved the lower extremity, 16% involved the upper extremity and 10% affected the back. In the lower extremity, the knee (49%), ankle (16%) and hip (11%) were most commonly affected. 80% of injuries were treated with physical therapy. Only 5% required surgical intervention. Injuries of both upper and lower extremities were more commonly seen on the athlete's dominant side, and the majority of injuries (77%) occurred in athletes 13 years or older. # Conclusion The majority of injuries in these fencing athletes affected the lower extremity, most commonly the knee. Extensor mechanism dysfunction, primarily patellofemoral pain, was the most common diagnosis. Hand dominance, patient age, and patient sex did affect different injury characteristics. # Level of Evidence 2b